2018
DOI: 10.21873/anticanres.12536
|View full text |Cite
|
Sign up to set email alerts
|

Disparities of Immunotherapy Utilization in Patients with Stage III Cutaneous Melanoma: A National Perspective

Abstract: Compared to other demographic factors, insurance status was associated with the greatest disparities in immunotherapy utilization and mortality for patients who underwent surgery for advanced melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…Ultimately, 44 studies met our inclusion criteria and were included in this systematic review ( Supplemental Figure S1 ). 2 , 4 , 6 , 10 , 14 - 53…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, 44 studies met our inclusion criteria and were included in this systematic review ( Supplemental Figure S1 ). 2 , 4 , 6 , 10 , 14 - 53…”
Section: Resultsmentioning
confidence: 99%
“…As multiple studies drew patient data from the same database, we pooled effect estimates from a representative study from each database with the longest timeframe from which patient data were drawn (HR 1.38, 95% CI, 1.10-1.73) ( Figure 1 ). 2 , 6 , 28 , 52 We also performed sensitivity analyses removing any studies using patient data from the Surveillance, Epidemiology, and End Results (SEER) program database (HR 1.29, 95% CI, 1.07-1.56), 6 , 28 , 51 , 52 and removing any studies with patient data from any national cancer database (HR 1.62, 95% CI, 1.20-2.19). 6 , 52 Overall, results of our meta-analyses suggest that black melanoma patients are significantly more likely to experience death from any cause compared to non-Hispanic white patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies 29 , 30 , 31 , 32 , 33 have analyzed the NCDB cohort before our analysis of the 2016 participant user file. These analyses evaluated the disparity in use of immunotherapy for all stages of melanoma in diagnosis years before 2013, 29 before 2014, 30 , 31 and in 2015 32 and for stage III disease.…”
Section: Discussionmentioning
confidence: 99%
“…These analyses evaluated the disparity in use of immunotherapy for all stages of melanoma in diagnosis years before 2013, 29 before 2014, 30 , 31 and in 2015 32 and for stage III disease. 33 These prior studies 29 , 30 , 31 , 32 , 33 indicated the presence of comorbidities, older age, government or no insurance, lower educational and income levels, and treatment at a community practice as factors associated with decreased receipt of immunotherapy. Our study further supports that many of these prior demographic factors may be associated with receipt of immunotherapy with the addition of cases diagnosed in 2015 and 2016.…”
Section: Discussionmentioning
confidence: 99%